Phosphatase PTPN22 Regulates Dendritic Cell Homeostasis and cDC2 Dependent T Cell Responses - Purvis, Harriet A.; Clarke, Fiona; Montgomery, Anna B.; Colas, Chloe; Bibby, Jack A.; Cornish, Georgina H.; Dai, Xuezhi; Dudziak, Diana; Rawlings, David J.; Zamoyska, Rose; Guermonprez, Pierre; Cope, Andrew P. (Frontiers in Immunology, 2020)
Dendritic cells (DCs) are specialized antigen presenting cells that instruct T cell responses through sensing environmental and inflammatory danger signals. Maintaining the homeostasis of the multiple functionally distinct conventional dendritic cells (cDC) subsets that exist in vivo is crucial for regulating immune responses, with changes in numbers sufficient to break immune tolerance. Using Ptpn22-/- mice we demonstrate that the phosphatase PTPN22 is a highly selective, negative regulator of cDC2 homeostasis, preventing excessive population expansion from as early as 3 weeks of age. Mechanistically, PTPN22 mediates cDC2 homeostasis in a cell intrinsic manner by restricting cDC2 proliferation. A single nucleotide polymorphism, PTPN22R620W, is one of the strongest genetic risk factors for multiple autoantibody associated human autoimmune diseases. We demonstrate that cDC2 are also expanded in mice carrying the orthologous PTPN22619W mutation. As a consequence, cDC2 dependent CD4+ T cell proliferation and T follicular helper cell responses are increased. Collectively, our data demonstrate that PTPN22 controls cDC2 homeostasis, which in turn ensures appropriate cDC2-dependent T cell responses under antigenic challenge. Our findings provide a link between perturbations in DC development and susceptibility to a broad spectrum of PTPN22R620W associated human autoimmune diseases.